Effect of hydrologic modification and interbasin water transfers on streamflow metrics affecting aquatic ecology in Arequipa, Peru - Fariborz Daneshvar; Jane R. Frankenberger; Laura C. Bowling; Keith A. Cherkauer; Hector Novoa; Edwin F. Bocardo Delgado (Journal of Hydrology: Regional Studies, 2025)
Study region: Department of Arequipa in Peru Study focus: Throughout the coastal department of Arequipa, Peru, extensive water infrastructure is used to redistribute water from the Andes highlands to the coastal desert and altiplano for use by urban populations and agriculture. Here we build on earlier simulations in an unregulated headwater to explicitly model the impact of water management on streamflow throughout the basin. These simulations can be the basis of estimating naturalized streamflow for the support of native populations of sensitive species in the coastal river reaches and highlands. The goal was to quantify the effect of complex and pervasive hydrologic modification and provide a tool for local water managers to assess the impact on streamflow metrics that impact aquatic ecology. New hydrological insights for the region: Simulated hydrologic metrics along the Camaná and Quilca-Chili Rivers show the complex interactive effects of the hydrologic modifications. Withdrawals for irrigation, the city, and especially transfers to other basins decrease low flows and increase flashiness, while the reservoirs reduce maximum flow and increase low flows. The hydrologic modifications are manifested differently at points along the stream channel which may have important implications for endemic aquatic species. An interactive online tool allows managers to assess the differences between naturalized and current flow at any location and visualize how current management is impacting the flow for specific reaches.